Adsorption of chromium (VI) by ethylenediamine-modified cross-linked magnetic chitosan resin: Isotherms, kinetics and thermodynamics - Hu, Xin-jiang; Wang, Jing-song; Liu, Yun-guo; Li, Xin; Zeng, Guang-ming; Bao, Zheng-lei; Zeng, Xiao-xia; Chen, An-wei; Long, Fei (Journal of hazardous materials, 2011)
The adsorption of chromium (VI) ions from aqueous solution by ethylenediamine-modified cross-linked magnetic chitosan resin (EMCMCR) was studied in a batch adsorption system. Chromium (VI) removal is pH dependent and the optimum adsorption was observed at pH 2.0. The adsorption rate was extremely fast and the equilibrium was established within 6–10 min. The adsorption data could be well interpreted by the Langmuir and Temkin model. The maximum adsorption capacities obtained from the Langmuir model are 51.813 mg g −1, 48.780 mg g −1 and 45.872 mg g −1 at 293, 303 and 313 K, respectively. The adsorption process could be described by pseudo-second-order kinetic model. The intraparticle diffusion study revealed that film diffusion might be involved in the present case. Thermodynamic parameters revealed the feasibility, spontaneity and exothermic nature of adsorption. The sorbents were successfully regenerated using 0.1 N NaOH solutions.